Methoprene and protein supplements accelerate reproductive development and improve mating success of male tephritid flies - Teal, P. E. A. (2013)
We have been studying the behavioural and physiological mechanisms associated with coordination of reproductive maturity and sex pheromone communication in male tephritid flies in order to develop methods for acceleration of reproductive maturity among sterilized males. Our studies revealed that exposure to the juvenile hormone analogue methoprene can accelerate the rate of sexual maturity in some but not all tephritid species tested. Additionally, we have determined that incorporation of protein hydrolysate into the adult diet improves sexual performance of sterile males. Coupling a diet enriched with protein hydrolysate for adult food and application of methoprene to adult males or pupae was found to advance significantly the age at which males of a number of species of flies from the genus Anastrepha and Bactrocera cucurbitae (Coquillet) become sexually mature and improve reproductive success of the males. These results have led to the development of a novel strategy to accelerate the reproductive development and increased competitiveness of mass-reared fruit flies for use in the sterile insect technique by incorporating methoprene treatment and protein hydrolysate diets into protocols for fruit fly emergence and release facilities. The following reviews research conducted to develop the system and our suggestions for use in improving efficacy of mating by sterile males destined for release in programmes to control some species of tephritid flies using the sterile insect technique.